Satellite Cell Depletion Disrupts Transcriptional Coordination and Muscle Adaptation to Exercise. Issue 1 (23rd November 2020) - Englund, Davis A; Figueiredo, Vandré C; Dungan, Cory M; Murach, Kevin A; Peck, Bailey D; Petrosino, Jennifer M; Brightwell, Camille R; Dupont, Alec M; Neal, Ally C; Fry, Christopher S; Accornero, Federica; McCarthy, John J; et al.
Abstract: Satellite cells are required for postnatal development, skeletal muscle regeneration across the lifespan, and skeletal muscle hypertrophy prior to maturity. Our group has aimed to address whether satellite cells are required for hypertrophic growth in mature skeletal muscle. Here, we generated a comprehensive characterization and transcriptome-wide profiling of skeletal muscle during adaptation to exercise in the presence or absence of satellite cells in order to identify distinct phenotypes and gene networks influenced by satellite cell content. We administered vehicle or tamoxifen to adult Pax7-DTA mice and subjected them to progressive weighted wheel running (PoWeR). We then performed immunohistochemical analysis and whole-muscle RNA-seq of vehicle (SC+) and tamoxifen-treated (SC−) mice. Further, we performed single myonuclear RNA-seq to provide detailed information on how satellite cell fusion affects myonuclear transcription. We show that while skeletal muscle can mount a robust hypertrophic response to PoWeR in the absence of satellite cells, growth, and adaptation are ultimately blunted. Transcriptional profiling reveals several gene networks key to muscle adaptation are altered in the absence of satellite cells. Graphical Abstract: